Parents' Efforts in Supporting A Child with Speech Delay - Nor Izzatil Hasanah; Hidayah Nor (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2023)
Language of a child continue to develop in accordance with stimulus from the surrounding environment particularly families (parents), teachers and community. This study aims to identify speech delay in terms of efforts of parents in stimulating their child by using a case study approach. Early intervention of the parents is critical for children with speech and language delays, as it can prevent further developmental delays and improve their communication skills. Parents play a crucial role in their child's language development and can make a significant difference by providing a supportive and stimulating environment for their child to learn and practice language skills. The participants in this study were child and parents and the data were collected through observation and interview. The results of this study indicated that the type of speech delay found were speech and language expressive disorder. The factors which contribute to speech delay are the lack of parental stimulation, the use of gadgets, the type of program the child watch on his gadget and the use of language in the program he watched. The study also discussed the efforts made by parents in stimulating child's language development including changing the style of communication (speaking softly and repetitively, not responding if only pointing or giving gestures when asked to respond, always involving child in speaking, changing the type of questions from YES/NO to WH questions), reading story before going to bed and asking child to respond by various questions, inviting child to play, always giving a picture book and color pencil and asking the child's work, and inviting child to therapy to a pediatrician on a regular basis once a week for 1 hour.